2016
DOI: 10.1111/bij.12774
|View full text |Cite
|
Sign up to set email alerts
|

Tempo and mode in the evolution of morphological disparity in the Neotropical fern genusPleopeltis

Abstract: Species diversity and morphological disparity are two measures to examine the diversity of life. Evidence based on the fossil record suggests a complex relation between these two parameters of biodiversity including frequent decoupling of their assembly through time. However, rather few studies explored the correlation of these two measurements by studying extant plant species. This study was designed to explore the accumulation of morphological disparity of the derived Neotropical fern genus Pleopeltis. To ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
4
0
1
Order By: Relevance
“…Some of these taxa may turn out to be the consequence of hybrid-speciation (e.g. Liu et al 2018) but other processes such as limitations to the accessible morphospace may contribute also to the accumulation of cryptic fern diversity (see Schneider 2016). The genus Scleroglossum as well as other grammitid ferns is arguably well suited to explore the role of rapid diversification and ecological conservatism in the decoupling of the accumulation of species diversity and morphological disparity (Schneider 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these taxa may turn out to be the consequence of hybrid-speciation (e.g. Liu et al 2018) but other processes such as limitations to the accessible morphospace may contribute also to the accumulation of cryptic fern diversity (see Schneider 2016). The genus Scleroglossum as well as other grammitid ferns is arguably well suited to explore the role of rapid diversification and ecological conservatism in the decoupling of the accumulation of species diversity and morphological disparity (Schneider 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al 2018) but other processes such as limitations to the accessible morphospace may contribute also to the accumulation of cryptic fern diversity (see Schneider 2016). The genus Scleroglossum as well as other grammitid ferns is arguably well suited to explore the role of rapid diversification and ecological conservatism in the decoupling of the accumulation of species diversity and morphological disparity (Schneider 2016). As shown by Liu et al (2018), the interpretation of DNA barcode based species identification may result in misleading species assessment if the ploidy level has not been assessed.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis has been supported by some recent macroevolutionary studies that found evidence for the 'early high-disparity' pattern of morphological evolution (Valentine et al, 1996;Wagner, 1997;Ruta et al, 2006;Hughes et al, 2013). Until recently, the majority of studies testing predictions on the assembly of morphological disparity focused on animals, and an increasing number of studies have made efforts in determining evolution of disparity in land plants, such as liverworts (Yu et al, 2014), ferns (Schneider, 2016) and angiosperms (Chartier et al, 2017). Only a few studies explored specifically the evolution of pollen morphological disparity, such as that of Mander (2016).…”
Section: Introductionmentioning
confidence: 85%
“…Epacridoideae (e.g. Styphelieae), with a distribution in Australia and adjacent islands, occupy the largest compartment in pollen morphospace and overlap extensively with other subfamilies, suggesting geographic isolation and/or environment range (Schneider, 2016;Chartier et al, 2017).…”
Section: Prediction 3: Dimension Of Pollen Disparity Uncorrelated Witmentioning
confidence: 99%
“…En contraste, un filomorfoespacio combina la filogenia (filograma, como en Mason et al 2016, Morello et al 2018 o el cronograma (como en Schneider 2016, Gaudioso et al 2020) con el morfoespacio (ejes de componentes principales o de variables canónicas) para trazar la diversificación de los rasgos fenotípicos, resultando en un gráfico que permite evaluar patrones fenotípicos multivariados (Adams & Collyer 2019). Una forma de evaluar estos patrones fenotípicos es midiendo la magnitud e innovación morfológica, lo que permite explorar hipótesis macroevolutivas y escenarios evolutivos (Sidlauskas 2008).…”
unclassified